Reproductive performance and larval quality of blue swimming crab (Portunus pelagicus) broodstock, fed with different feeds - Vutthichai Oniam; Likhit Chuchit; Wasana Arkronrat (Songklanakarin Journal of Science and Technology (SJST), 2012)
Fecundity, hatching rate and crab larvae quality of blue swimming crab, Portunus pelagicus, broodstock reared inearthen ponds, fed with different feeds, were studied for about 150 days. Results showed that average fecundity ofP. pelagicus broodstock fed with trash fish (569,842±243,173 eggs), shrimp feed (464,098±188,884 eggs), mixed feeds(544,875.3±169,357.3 eggs) and hatching rate (50.78±25.19%, 62.33±26.79% and 50.86±20.76%) were not significantly different(P>0.05). Zoea produced by female broodstock fed with mixed feeds had a significantly higher survival rate (89.47±5.03%,P<0.05) compared to those produced by female broodstock fed with trash fish (73.40±14.61%) and shrimp feeds (67.33±12.80%), but the survival rate of megalopa and first crab stages was not affected. This study recommends that the mixed feedwas suitable feed for rearing of P. pelagicus broodstock in an earthen pond as evidenced by the quality of zoea I or 1 dayafter hatching and growth of female broodstock.